2019
DOI: 10.1002/mar.21215
|View full text |Cite
|
Sign up to set email alerts
|

Preservation, rejuvenation, or confusion? Changing package designs for heritage brands

Abstract: Updating a brand's packaging presents a challenge, especially for heritage brands. This study examines how and when continuity in visual package design influences brand heritage perceptions. A pre‐study uses focus groups to corroborate evidence for the constructs and processes involved. Three experiments show that lower continuity designs create confusion, which in turn damages a brand's heritage identity. Study 1a provides initial evidence for the process and demonstrates that effects occur regardless of prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…It extends the theoretical streams that deal with the purchase motives of luxury brand consumers (Bian and Forsythe, 2012;Grewal et al, 2004;Prentice and Loureiro, 2018;Schade et al, 2016;Wilcox et al, 2009). It also contributes to the literature on heritage that examined consumer behavior (Brunninge and Hartmann, 2019;Dion and Borraz, 2015;Dion and Mazzalovo, 2016;Orth et al, 2019;Pecot and De Barnier, 2018;Riley et al, 2004;Wuestefeld et al, 2012).…”
mentioning
confidence: 69%
“…It extends the theoretical streams that deal with the purchase motives of luxury brand consumers (Bian and Forsythe, 2012;Grewal et al, 2004;Prentice and Loureiro, 2018;Schade et al, 2016;Wilcox et al, 2009). It also contributes to the literature on heritage that examined consumer behavior (Brunninge and Hartmann, 2019;Dion and Borraz, 2015;Dion and Mazzalovo, 2016;Orth et al, 2019;Pecot and De Barnier, 2018;Riley et al, 2004;Wuestefeld et al, 2012).…”
mentioning
confidence: 69%
“…In a subsequent study, Pecot et al (2019) found that brand heritage enhanced brand credibility and personal nostalgia. Orth et al (2019) studied package designs for [product] heritage brands and found that lower continuity designs created confusion among customers, which in turn damaged a brand's heritage identity. Rindell (2013Rindell ( , 2017 conceptualised the time dimension in branding research from a consumer perspective as image heritage in order to understand how consumers' past perceptions of a brand would influence their present image construction processes and future expectations.…”
Section: Corporate Heritage Researchmentioning
confidence: 99%
“…The role of packaging for consumers is becoming the main tool for communication and branding [22]. Special attention should be paid to packaging elements for their impact on consumer feedback [23]. Color as a packaging element encourages consumers to appreciate the product more, especially for healthy products [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Color as a packaging element encourages consumers to appreciate the product more, especially for healthy products [24]. Thus, frequent changes to packaging elements can disorient the consumer, affecting the perception of brands [23].…”
Section: Literature Reviewmentioning
confidence: 99%